KRAS mutation: The booster of pancreatic ductal adenocarcinoma transformation and progression - Zhang, Zining; Zhang, Heng; Liao, Xiang; Tsai, Hsiang-i (Frontiers in Cell and Developmental Biology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer. It has a poor response to conventional therapy and has an extremely poor 5-year survival rate. PDAC is driven by multiple oncogene mutations, with the highest mutation frequency being observed in KRAS. The KRAS protein, which binds to GTP, has phosphokinase activity, which further activates downstream effectors. KRAS mutation contributes to cancer cell proliferation, metabolic reprogramming, immune escape, and therapy resistance in PDAC, acting as a critical driver of the disease. Thus, KRAS mutation is positively associated with poorer prognosis in pancreatic cancer patients. This review focus on the KRAS mutation patterns in PDAC, and further emphases its role in signal transduction, metabolic reprogramming, therapy resistance and prognosis, hoping to provide KRAS target therapy strategies for PDAC.